(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: В статье рассматривается влияние технологий искусственного интеллекта (ИИ) на экономическую безопасность предприятий. Автор анализирует как позитивные эффекты цифровизации, включая автоматизацию процессов и повышение эффективности управления, так и потенциальные угрозы, связанные с киберрисками, технологической зависимостью и социальной нестабильностью. На основе проведенного анализа предложены меры по обеспечению устойчивости бизнеса при внедрении ИИ-технологий. This article examines the impact of artificial intelligence (AI) technologies on the economic security of modern enterprises. The paper highlights both the positive effects of AI implementation — including process automation, cost reduction, and improved cybersecurity — and the emerging risks associated with data breaches, technological dependence, and labor market disruptions. The dual role of AI as a tool for both increasing operational efficiency and generating new threats is emphasized. Based on the conducted analysis, the author proposes a set of measures to ensure enterprise resilience and economic security in the context of digital transformation.